Diversifikasi Kebutuhan Ternak Ruminansia Melalui Budidaya Rusa Sambar (Cervus unicolor): Tinjauan Aspek Fisiologis - Maksudi, Maksudi; Lukman, Haris; Rahayu, Pudji (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The  research  was  conducted  to  evaluate  the  effects  of  domestication  of  Sambar  deer  (Cervus unicolor)  on  performance  and  hematological  values.  One  captive  Sambar  deer  was  housed  in  an individual cages fitted on a slatted floor of 2 x 3 m2 . The diet was consisted of field grasses, legume and forages  given  ad  libitum  and  sweat  potatoes.  The  data  were  collected  during  a  two-month  period following a one-month adaptation period; The feed and the residues were collected daily, and the blood samples for hematological values were collected via jugular vein. The data were obtained three times; at the beginning (0 month), in the middle (1 month), and in the end (2 months) of the trial. The performance results showed  that BW  in  the  three respective  times were 12.17, 15.60 and 19.40 kg; ADG in  the  first and the second month respectively ware 115 dan 127 gr/d; Total of DM consumption were 987 and 1216 gr/d;  and  the  percentage  of DM/BW  were  6,33  dan  6,27%.  The  following  averages  of  hematological values were obtained: erythrocytes 8,4, 7,9 dan 7,9 million/ml;  Hemoglobin 11,4, 11,2 and 13,2 gr/100 ml;    PCV  0,62,  0,57  and  0.50%;  Leukosytes  14750,  11547  and  9721/ml;  pH  7,34,  7,45  and  7,40, respectively.  Finally,  Sambar  deer  as  the  wild  animals  have  prospective  values  when  they  are domesticated and intensively cared.